Fluorescent dental hardenable composition and hardened product thereof
The dental curable composition, featuring a 9- to 11-membered benzo-fused heterocycle-containing compound, addresses the challenges of achieving fluorescent properties, aesthetics, and mechanical strength, resulting in a composition suitable for dental applications.
Patent Information
- Application Number
- JP2021565633
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-17
- Filing Date
- 2020-12-16
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2040-12-16
AI Technical Summary
Existing dental curable compositions struggle to achieve sufficient fluorescent properties, excellent aesthetics, durability, mechanical strength, X-ray contrast, and easy abrasiveness, especially when used with fillers like zirconia.
A dental curable composition comprising a polymerizable monomer, an inorganic filler, a polymerization initiator, and a fluorescent agent that includes a 9- to 11-membered benzo-fused heterocycle-containing compound, which provides enhanced fluorescent properties and mechanical strength.
The composition achieves sufficient fluorescent properties, excellent aesthetics, durability, mechanical strength, X-ray contrast, and easy abrasiveness, making it suitable for dental composite resins and mill blanks.
Smart Images

Figure 0007663511000001 
Figure 0007663511000002 
Figure 0007663511000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a dental hardenable composition that can be suitably used in the field of dentistry as a dental material capable of partially or completely replacing natural teeth, particularly as a dental composite resin or a dental mill blank. [Background technology]
[0002] Natural teeth have fluorescence, and therefore appear bright under natural light, but pale under black light. Therefore, when a dental material that does not have fluorescence and is made of a hardenable composition containing a polymerizable monomer, a polymerization initiator, etc. is used in dental restorative treatment, the natural teeth and the restored part made of the dental material may have different colors depending on the surrounding environment, making them easy to distinguish. In recent years, dental materials are required to have high aesthetics, so that the restored part is indistinguishable from the natural teeth under any environment. In order to improve aesthetics, it has been proposed to add an organic fluorescent dye to the dental material to give the dental material the same fluorescence as the natural teeth.
[0003] For example, Patent Documents 1 and 2 disclose dental materials that contain a phthalate ester-based fluorescent agent such as 2,5-dihydroxydiethyl terephthalate, with the aim of imparting fluorescence equivalent to that of natural teeth.
[0004] However, it is known that when the phthalate ester-based fluorescent agents described in Patent Documents 1 and 2 are present in a dental hardenable composition containing a specific component, specifically, in a dental hardenable composition containing a filler containing zirconia, alumina, or the like, the hardened product obtained by polymerization and hardening becomes more yellowish, making it difficult to reproduce the color tone of natural teeth.
[0005] In order to solve such problems, Patent Document 3 proposes a curable composition in which the contents of an amine compound, a phthalate ester-based fluorescent agent, and an X-ray contrast acidic filler are specified. However, the present inventors have found that the composition described in Patent Document 3 does not provide sufficient fluorescence under clinical conditions, and therefore there is room for further improvement in this regard.
[0006] In addition, Patent Document 4 proposes an inorganic fluorescent agent that does not discolor even when coexisting with zirconia. However, it is generally known that the smaller the particle size of an inorganic fluorescent agent is, the lower the fluorescent intensity is, and in order to ensure sufficient fluorescence, it is necessary to include the inorganic fluorescent agent in the dental curable composition as coarse particles of several μm in size. In dental composite resins and dental CAD / CAM resin blocks, the inclusion of such coarse inorganic fluorescent particles can cause abrasiveness and mechanical strength to decrease, fluorescence unevenness, and the like. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 2-233605 [Patent Document 2] JP 2009-280673 A [Patent Document 3] JP 2017-141188 A [Patent Document 4] JP 2010-222466 A Summary of the Invention [Problem to be solved by the invention]
[0008] As described above, in the prior art, a dental hardenable composition and a hardened product thereof that have sufficient fluorescence, excellent aesthetics and durability, sufficient mechanical strength and X-ray contrast properties, and do not impair ease of polishing have not been found.
[0009] The present invention has been made to solve the above-mentioned problems associated with the conventional techniques, and an object of the present invention is to provide a dental hardenable composition, which has sufficient fluorescence, enables highly aesthetic restorations that blend in with the surroundings to the extent that they are indistinguishable from natural teeth, has excellent resistance to discoloration in the oral environment, under accelerated heating conditions, and under xenon lamp light exposure conditions, does not lose its fluorescence even under such conditions, and has sufficient mechanical strength and X-ray contrast properties as a restoration, and good polishability, as well as a hardened product thereof. [Means for solving the problem]
[0010] Means for Solving the Problems The present inventors have conducted extensive research to achieve the above object, and as a result have found that a dental hardenable composition containing a compound having a specific structure, and a cured product thereof, have sufficient fluorescence, excellent aesthetics and durability, sufficient mechanical strength and X-ray contrast properties, and do not impair ease of polishing.
[0011] That is, the present invention includes the following inventions. [1] A dental curable composition comprising a polymerizable monomer (A), an inorganic filler (B), a polymerization initiator (C), and a fluorescent agent (D), wherein the fluorescent agent (D) comprises a 9- to 11-membered benzo-fused heterocycle-containing compound having two or more heteroatoms (excluding benzimidazole compounds). [2] The dental curable composition according to [1], wherein the 9- to 11-membered benzo-fused heterocycle-containing compound having two or more heteroatoms includes a fluorescent agent (D-1) which is a 6-membered benzo-fused heterocycle-containing compound having two heteroatoms. [3] The dental hardenable composition according to [2], wherein the fluorescent agent (D-1) contains a compound having a benzodiazinone skeleton and / or a compound having a benzoxazinone skeleton. [4] The dental hardenable composition according to [3], wherein the compound having a benzodiazinone skeleton is a compound having a skeleton represented by the following general formula (5): [ka] (In the general formula (5), X represents a six-membered heterocyclic ring containing two nitrogen atoms, and the six-membered heterocyclic ring has at least one oxo group and may have a substituent.) [5] The dental hardenable composition according to [3] or [4], wherein the compound having a benzodiazinone skeleton is a compound (D-1a) having a quinazolinone skeleton. [6] The dental hardenable composition according to [3], wherein the fluorescent agent (D-1) contains a compound having a benzoxazinone skeleton. [7] The dental hardenable composition according to [6], wherein the compound having a benzoxazinone skeleton is a compound having a skeleton represented by the following general formula (6): [ka] (In the general formula (6), Y represents a six-membered heterocyclic ring containing one nitrogen atom and one oxygen atom, and the six-membered heterocyclic ring has at least one oxo group and may have a substituent.) [8] The dental curable composition according to any one of [2] to [7], wherein the fluorescent agent (D-1) is a compound having a moiety represented by the following general formula (1) or (2): [ka] [ka] (R in general formulas (1) and (2) 1 is an oxygen atom or -NH-, R 2 represents an aromatic group which may have a substituent. [9] The fluorescent agent (D-1) is 2-(2-hydroxyphenyl)-4(1H)-quinazolinone, 2-(2-hydroxyphenyl)-4H-3,1-benzoxazin-4-one, N-[2-(4(1H)-quinazolinon-2-yl)phenyl]benzenesulfonamide, N-[2-(4-oxo-1,3-benzoxazin-2-yl)phenyl]benzenesulfonamide, 7-dimethylamino-3-[2-[4-(trifluoromethyl)phenyl]ethenyl] The dental hardenable composition according to any one of [2] to [7], comprising at least one compound selected from the group consisting of 7-dimethylamino-3-[2-[2,3,4,5,6-pentafluorophenyl]ethenyl]-2H-1,4-benzoxazin-2-one, 7-dimethylamino-3-[2-[2,4-bis(trifluoromethyl)phenyl]ethenyl]-2H-1,4-benzoxazin-2-one, and 7-dimethylamino-3-[2-[2,4-bis(trifluoromethyl)phenyl]ethenyl]-2H-1,4-benzoxazin-2-one.
[10] The dental hardenable composition according to any one of [2] to [9], wherein the fluorescent agent (D) further contains a fluorescent agent (D-2) which is a benzo-fused heterocyclic 5-membered ring-containing compound containing one nitrogen atom and one oxygen atom.
[11] The dental hardenable composition according to
[10] , wherein the fluorescent agent (D-2) is a fluorescent agent (D-2a) that is a compound containing a benzoxazole skeleton.
[12] The dental curable composition according to
[11] , wherein the fluorescent agent (D-2a) is a compound having a moiety represented by the following general formula (3): [ka] (In general formula (3), R 3 represents an aromatic group which may have a substituent, or a vinylene group which may have a substituent.
[13] The dental curable composition according to
[11] or
[12] , wherein the fluorescent agent (D-2a) is a compound represented by the following formula (12): [ka]
[14] The dental hardenable composition according to any one of [1] to
[13] , wherein the inorganic filler (B) is an inorganic filler containing at least one metal compound selected from the group consisting of zirconium oxide, aluminum oxide, ytterbium oxide, and ytterbium fluoride.
[15] The specific surface area of the inorganic filler (B) is 10 to 300 m 2 / g of the dental hardenable composition according to any one of [1] to
[14] .
[16] A dental composite resin, comprising the dental hardenable composition according to any one of [1] to
[15] .
[17] A dental mill blank, comprising a cured product of the dental hardenable composition according to any one of [1] to
[15] . Effect of the Invention
[0012] According to the present invention, there can be provided a dental hardenable composition and a cured product thereof, which have sufficient fluorescence, can be used for highly aesthetic restorations that blend in with the surroundings to the extent that they are indistinguishable from natural teeth, have excellent resistance to discoloration in the oral cavity, under accelerated heating conditions, and under xenon lamp light exposure conditions, do not lose their fluorescence even under such conditions, and have sufficient mechanical strength and X-ray contrast properties as a restoration, and good polishability. In addition, the dental hardenable composition and the cured product thereof of the present invention can be suitably used for dental composite resins, dental mill blanks, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention will be described in detail below. The dental curable composition of the present invention contains a polymerizable monomer (A), an inorganic filler (B), a polymerization initiator (C), and a fluorescent agent (D), and the fluorescent agent (D) contains a 9- to 11-membered benzo-fused heterocycle-containing compound (excluding benzimidazole compounds) containing two or more heteroatoms. By adopting the above-mentioned constitution, the dental curable composition and its cured product, which have sufficient fluorescence, excellent aesthetics and durability, sufficient mechanical strength, X-ray contrast property, and easy polishing property, are suitable for dental composite resins, dental mill blanks, etc.
[0014] [Polymerizable monomer (A)] As the polymerizable monomer (A) in the dental hardenable composition of the present invention, a known polymerizable monomer used in a dental hardenable composition can be used, and in particular, a radically polymerizable monomer can be preferably used. Examples of the radically polymerizable monomer include esters of unsaturated carboxylic acids such as α-cyanoacrylic acid, (meth)acrylic acid, α-halogenated acrylic acid, crotonic acid, cinnamic acid, sorbic acid, maleic acid, and itaconic acid; (meth)acrylamide; (meth)acrylamide derivatives; vinyl esters; vinyl ethers; mono-N-vinyl derivatives; and styrene derivatives. The polymerizable monomer (A) may be used alone or in combination of two or more kinds. Among these, esters of unsaturated carboxylic acids and (meth)acrylamide derivatives are preferred, (meth)acrylic acid esters and (meth)acrylamide derivatives are more preferred, and (meth)acrylic acid esters are even more preferred. In this specification, the term "(meth)acrylic" is used to include both methacryl and acrylic. The term "(meth)acrylic monomer" is used to include both (meth)acrylic acid esters and (meth)acrylamide derivatives. Examples of (meth)acrylic acid esters and (meth)acrylamide derivatives are shown below.
[0015] (i) Monofunctional (meth)acrylic acid ester and (meth)acrylamide derivatives For example, methyl (meth)acrylate, isobutyl (meth)acrylate, benzyl (meth)acrylate, dodecyl (meth)acrylate, 2-(N,N-dimethylamino)ethyl (meth)acrylate, 2,3-dibromopropyl (meth)acrylate, 3-(meth)acryloyloxypropyltrimethoxysilane, 11-(meth)acryloyloxyundecyltrimethoxysilane, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate. , 10-hydroxydecyl (meth)acrylate, propylene glycol mono(meth)acrylate, glycerin mono(meth)acrylate, erythritol mono(meth)acrylate, phenoxyethylene glycol (meth)acrylate, isobornyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, N-methylol (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N,N-bis(hydroxyethyl) (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-di-n-propyl(meth)acrylamide, N-ethyl-N-methyl(meth)acrylamide, (meth)acryloylmorpholine, (meth)acryloyloxydodecylpyridinium bromide, (meth)acryloyloxydodecylpyridinium chloride, (meth)acryloyloxyhexadecylpyridinium bromide, (meth)acryloyloxyhexadecylpyridinium chloride, ethoxylated-o-phenylphenol(meth)acrylate, ethoxylated-m-phenylphenol(meth)acrylate, ethoxylated-p-phenylphenol(meth) Examples of suitable acrylates include propoxylated o-phenylphenol (meth)acrylate, propoxylated m-phenylphenol (meth)acrylate, propoxylated p-phenylphenol (meth)acrylate, o-phenoxybenzyl (meth)acrylate, m-phenoxybenzyl (meth)acrylate, p-phenoxybenzyl (meth)acrylate, 2-(o-phenoxyphenyl)ethyl (meth)acrylate, 2-(m-phenoxyphenyl)ethyl (meth)acrylate, and 2-(p-phenoxyphenyl)ethyl (meth)acrylate. Among these, ethoxylated o-phenylphenol (meth)acrylate and m-phenoxybenzyl (meth)acrylate are most preferred, in that the paste of the dental hardenable composition obtained has good operability and excellent mechanical strength after hardening.
[0016] (ii) Difunctional (meth)acrylic acid ester For example, aromatic bifunctional (meth)acrylic esters and aliphatic bifunctional (meth)acrylic esters are included.
[0017] Examples of aromatic bifunctional (meth)acrylic acid esters include 2,2-bis((meth)acryloyloxyphenyl)propane, 2,2-bis[4-(3-acryloyloxy-2-hydroxypropoxy)phenyl]propane, 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (commonly known as Bis-GMA), 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxyethoxyphenyl)propane, 2-(4-(meth)acryloyloxydiethoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2- Examples of the acryloyloxypropoxyphenyl include bis(4-(meth)acryloyloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2-(4-(meth)acryloyloxydipropoxyphenyl)-2-(4-(meth)acryloyloxytriethoxyphenyl)propane, 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, 9,9-bis[4-(2-(meth)acryloyloxypolyethoxy)phenyl]fluorene, diphenylbis[3-(meth)acryloyloxypropyl]silane, and methylphenylbis[3-(meth)acryloyloxypropyl]silane.
[0018] Examples of the aliphatic difunctional (meth)acrylic acid esters include glycerol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate (commonly known as 3G), propylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and the like. tert-acrylate, 1,10-decanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropyloxy)ethane, tricyclodecane dimethanol di(meth)acrylate, 2,2,4-trimethylhexamethylene bis(2-carbamoyloxyethyl)diacrylate, 2,2,4-trimethylhexamethylene bis(2-carbamoyloxyethyl)dimethacrylate (commonly known as UDMA), dicyclohexyl bis[3-(meth)acryloyloxypropyl]silane, and the like.
[0019] Among the above-mentioned bifunctional (meth)acrylic acid esters, 2,2-bis[4-(3-acryloyloxy-2-hydroxypropoxy)phenyl]propane, 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (Bis-GMA), 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane (average number of moles of ethyleneoxy groups added: 1 to 30), and 2,2-bis[4-(meth)acryloyloxypolyethoxyphenyl]propane (average number of moles of ethyleneoxy groups added: 1 to 30) are preferred because they improve the handleability of the dental hardenable composition and the mechanical strength of the obtained hardened product. Triethylene glycol diacrylate, triethylene glycol dimethacrylate (3G), 1,10-decanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropyloxy)ethane, tricyclodecane dimethanol di(meth)acrylate, 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)diacrylate, 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)diacrylate Preferred are 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (Bis-GMA), 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (average number of moles of ethyleneoxy groups added: 1 to 30), triethylene glycol dimethacrylate (3G), 1,10-decanediol dimethacrylate, 1,12-dodecanediol dimethacrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropyloxy)phenyl)dimethacrylate (UDMA), and preferred are 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (Bis-GMA), 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (average number of moles of ethyleneoxy groups added: 1 to 30), triethylene glycol dimethacrylate (3G), 1,10-decanediol dimethacrylate, 1,12-dodecanediol dimethacrylate, 1,2-bis(3-methacryloyloxy-2-hydroxypropyloxy)phenyl)dimethacrylate, (iii) Ethane, tricyclodecane dimethanol dimethacrylate, and 2,2,4-trimethylhexamethylene bis(2-carbamoyloxyethyl) dimethacrylate (UDMA) are more preferred, and 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane (Bis-GMA), 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (having an average added mole number of ethyleneoxy groups of about 2.6), and triethylene glycol dimethacrylate (3G) are even more preferred.
[0020] (iii) Tri- or higher functional (meth)acrylic acid ester For example, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, N,N'-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetra(meth)acrylate, 1,7-di(meth)acryloyloxy-2,2,6,6-tetra(meth)acryloyloxymethyl-4-oxaheptane, and the like can be mentioned.
[0021] In addition, since the polymerizable monomer (A) results in a dental curable composition with excellent adhesion to teeth, metals, ceramics, etc., it may be preferable in some cases to contain a functional monomer that can impart adhesion to these adherends.
[0022] Examples of the functional monomer, which exhibit excellent adhesion to teeth and base metals, include polymerizable monomers having a phosphate group, such as 2-(meth)acryloyloxyethyl dihydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, and 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate; and polymerizable monomers having a carboxylic acid group, such as 11-(meth)acryloyloxyundecane-1,1-dicarboxylic acid and 4-(meth)acryloyloxyethoxycarbonyl phthalic acid. In addition, from the viewpoint of excellent adhesion to precious metals, examples of the agent include 10-mercaptodecyl (meth)acrylate, 6-(4-vinylbenzyl-n-propyl)amino-1,3,5-triazine-2,4-dithione, thiouracil derivatives described in JP-A-10-1473, and compounds having elemental sulfur described in JP-A-11-92461, etc. Furthermore, from the viewpoint of effective adhesion to ceramics, porcelain materials, and other dental hardenable compositions, examples of the agent include silane coupling agents such as γ-(meth)acryloyloxypropyltrimethoxysilane, etc.
[0023] The content of the polymerizable monomer (A) in the dental curable composition of the present invention is not particularly limited, but from the viewpoint of the operability of the dental curable composition obtained and the mechanical strength of the cured product, it is preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 5% by mass or more, 8% by mass or more, and even 15% by mass or more based on the total mass of the dental curable composition, and it is preferably 70% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, and particularly preferably 30% by mass or less. In addition, the content of the polymerizable monomer (A) in the dental curable composition of the present invention is preferably 3 parts by mass or more, more preferably 4 parts by mass or more, even more preferably 5 parts by mass or more, particularly preferably 10 parts by mass or more, and preferably 90 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less, and particularly preferably 35 parts by mass or less, based on the total mass of 100 parts by mass of the polymerizable monomer (A) and the inorganic filler (B).
[0024] [Inorganic filler (B)] The dental hardenable composition of the present invention contains an inorganic filler (B).
[0025] The average particle size of the inorganic filler (B) is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and may be 0.2 μm or more, and is preferably 50 μm or less, more preferably 20 μm or less, even more preferably 10 μm or less, and particularly preferably 7 μm or less. When the average particle size of the inorganic filler (B) is the above lower limit or more, the stickiness of the dental hardenable composition obtained can be more effectively suppressed, and the operability is improved. When the average particle size of the inorganic filler (B) is the above upper limit or less, the sagging and roughness of the dental hardenable composition obtained can be more effectively suppressed, and the operability is improved. In addition, when the inorganic filler (B) is an aggregated particle (secondary particle), the average particle size of the inorganic filler (B) means the average particle size of the aggregated particle (secondary particle).
[0026] The average particle size of the inorganic filler (B) can be determined by a laser diffraction scattering method or by observing the particles under an electron microscope. Specifically, the laser diffraction scattering method is convenient for measuring the particle size of particles of 0.1 μm or more, and the electron microscope observation is convenient for measuring the particle size of ultrafine particles of less than 0.1 μm. 0.1 μm is a value measured by the laser diffraction scattering method. The laser diffraction scattering method can be measured on a volume basis using ethanol or a 0.2% aqueous solution of sodium hexametaphosphate as a dispersion medium, for example, with a laser diffraction type particle size distribution measuring device (such as "SALD-2300" manufactured by Shimadzu Corporation). For electron microscope observation, a scanning electron microscope (such as SU3800 or S-4000 manufactured by Hitachi High-Technologies Corporation) can be used. Specifically, the electron microscope observation can be performed by taking an electron microscope photograph of the particles and measuring the particle size of the particles (200 or more) observed in a unit field of view of the photograph using image analysis type particle size distribution measurement software (Mac-View (manufactured by Mountec Co., Ltd.)). At this time, the particle size is obtained as the arithmetic mean value of the longest and shortest lengths of the particles, and the average primary particle size is calculated from the number of particles and their particle size. More specifically, the average particle size of the inorganic filler (B) can be measured by the method described in the Examples.
[0027] The overall shape of the particles of the inorganic filler (B) is not particularly limited, and it can be used as an amorphous or spherical powder. When an amorphous inorganic filler (B) is used, a dental hardenable composition having particularly excellent mechanical strength and abrasion resistance of the cured product can be obtained, and when a spherical inorganic filler (B) is used, a dental hardenable composition having smooth paste properties, good spreadability, and excellent operability can be obtained. The overall shape of the inorganic filler (B) may be appropriately selected depending on the purpose of the dental hardenable composition.
[0028] Examples of the inorganic filler (B) include various glasses (mainly composed of silica, and optionally containing oxides of heavy metals, boron, aluminum, etc., such as fused silica, quartz, soda lime silica glass, E glass, C glass, and borosilicate glass (Pyrex (registered trademark) glass) and other glass powders of general composition; barium glass (GM27884, 8235, manufactured by Schott, E-2000, E-3000, manufactured by ESSTECH), strontium borosilicate glass (E-4000, manufactured by ESSTECH), lanthanum glass ceramics (GM31684, manufactured by Schott), fluoroaluminosilicate glass (GM35429, G018-091, G0 Examples of the fillers include dental glass powders such as 18-117 (manufactured by Schott), various ceramics, composite oxides such as alumina, silica-titania, silica-zirconia, and silica-ytterbia, diatomaceous earth, kaolin, clay minerals (such as montmorillonite), activated clay, synthetic zeolite, mica, calcium fluoride, ytterbium fluoride, yttrium fluoride, calcium phosphate, barium sulfate, zirconium oxide, titanium oxide, and hydroxyapatite. These may be used alone or in combination of two or more. Among these, those containing silica as the main component (those containing 5% by mass or more of silica, preferably 10% by mass or more) are suitable. Among these, inorganic fillers containing metal compounds such as zirconium oxide, aluminum oxide, and ytterbium oxide, which have high X-ray contrast properties (barium glass, alumina, silica-titania, silica-zirconia, silica-ytterbia, etc.), and ytterbium fluoride are preferred.
[0029] In the present invention, the specific surface area of the inorganic filler (B) tends to be high in abrasiveness, so it is preferable to set the specific surface area to 10 m 2 / g or more is preferable, and 15m 2 / g or more is more preferable, and 18m 2 More preferably, it is 20m 2 / g or more is particularly preferable, and 300m 2 / g or less, 250m 2 / g or less, and 2 / g or less is more preferable, and 2 / g or less, 170m 2 / g or less, and even 150m 2 / g or less. When the specific surface area of the inorganic filler (B) is equal to or more than the lower limit, the polishability is further improved. When the specific surface area of the inorganic filler (B) is equal to or less than the upper limit, the amount of the inorganic filler (B) can be increased, and the mechanical strength of the obtained cured product is improved. When the inorganic filler (B) is an agglomerated particle (secondary particle), the specific surface area of the inorganic filler (B) means the specific surface area of the agglomerated particle (secondary particle).
[0030] The specific surface area of the inorganic filler (B) can be determined by the BET method. Specifically, for example, it can be measured using a specific surface area measuring device (such as the "BELSORP-mini" series manufactured by Microtrack-Bell Co., Ltd.). In determining the specific surface area of the inorganic filler (B) as described above, when the inorganic filler (B) is surface-treated as described below or is an organic-inorganic composite filler, it is preferable to measure the specific surface area after ashing the inorganic filler (B) in advance, for example, by treating it at 450°C for 4 hours, from the viewpoint of eliminating the influence of the organic matter. It is also preferable to perform ashing in the same manner when determining the specific surface area of the inorganic filler (B) contained in the dental curable composition. More specifically, the specific surface area of the inorganic filler (B) can be measured by the method described in the examples.
[0031] In the present invention, the inorganic filler (B) may be in the form of aggregated particles formed by aggregation of the inorganic filler. Usually, commercially available inorganic fillers exist as aggregates, but when 10 mg of inorganic filler powder is added to 300 mL of water or water (dispersion medium) containing 5 mass % or less of a surfactant such as sodium hexametaphosphate, and dispersed for 30 minutes with an ultrasonic intensity of 40 W and 39 KHz, the aggregated particles have only a weak cohesive force that allows them to be dispersed to the particle size indicated by the manufacturer. However, the aggregated particles in the present invention are particles that are hardly dispersed even under such conditions and are firmly aggregated together.
[0032] As a method for preparing agglomerated particles in which particles are strongly agglomerated from commercially available inorganic filler agglomerated particles, a method is preferably used in which the inorganic filler is heated to a temperature just before melting in order to further increase the agglomeration force, and the inorganic filler particles that come into contact with each other are heated to a temperature such that they are slightly fused together. In this case, in order to control the shape of the agglomerated particles, the agglomerated form may be created before heating. For example, the inorganic filler is placed in a suitable container and pressurized, or dispersed in a solvent once, and then the solvent is removed by a method such as spray drying.
[0033] In addition, as another suitable method for producing aggregated particles in which inorganic filler particles are strongly aggregated, silica sol, alumina sol, titania sol, zirconia sol, etc. produced by a wet method can be used, and this can be dried by freeze-drying, spray drying, etc., and then heated as necessary to easily obtain aggregated particles in which particles are strongly aggregated. Specific examples of sols include silica spherical fine particles (product name "Sea Hoster (registered trademark)" (KE series, surface treatment type, etc.; all of which are manufactured by Nippon Shokubai Co., Ltd.)), silica organosol (product name "OSCAL (registered trademark)"; manufactured by JGC Catalysts and Chemicals Co., Ltd.), titania sol (product name "QUEEN TITANIC" series; manufactured by Nissan Chemical Industries, Ltd.), silica sol (product name "Snowtex (registered trademark)"; manufactured by Nissan Chemical Industries, Ltd.), alumina sol (product name "Alumina Sol-100", "Alumina Sol-200", "Alumina Sol-520"; all of which are manufactured by Nissan Chemical Industries, Ltd.), and zirconia sol (product name "Nanouse (registered trademark) ZR" series; manufactured by Nissan Chemical Industries, Ltd.). The shape of the inorganic filler particles is not particularly limited, and can be appropriately selected for use.
[0034] In the present invention, the inorganic filler (B) may be contained in the dental hardenable composition as an organic-inorganic composite filler. The organic-inorganic composite filler refers to a filler containing the inorganic filler and a polymer of a polymerizable monomer.
[0035] In the present invention, the organic-inorganic composite filler is preferably an inorganic filler having an average particle size of 5 μm or less dispersed in an organic matrix, and the average particle size of the inorganic filler is more preferably 2 μm or less, and even more preferably 1 μm or less.
[0036] The method for producing the organic-inorganic composite filler in the present invention is not particularly limited. For example, a known polymerizable monomer and a known polymerization initiator may be added to the inorganic filler in advance to form a paste, which is then polymerized by solution polymerization, suspension polymerization, emulsion polymerization, or bulk polymerization, and pulverized to produce the filler.
[0037] There is no particular restriction on the refractive index of the inorganic filler (B), but by approximating the refractive index of the components other than the inorganic filler (B) in the dental hardenable composition, it is easy to increase the transparency of the obtained cured product. For this reason, the refractive index of the inorganic filler (B) is preferably 1.45 or more, more preferably 1.50 or more, even more preferably 1.51 or more, and preferably 1.63 or less, more preferably 1.60 or less, and even more preferably 1.58 or less. The refractive index of the inorganic filler (B) can be controlled by adjusting the type and ratio of the metal elements contained therein.
[0038] The inorganic filler (B) may not be surface-treated, but is preferably surface-treated because the surface of the inorganic filler (B) is hydrophobized to improve the affinity with the polymerizable monomer (A), and the amount of the inorganic filler (B) can be increased. The surface treatment can be performed using a surface treatment agent. There is no particular restriction on the type of the surface treatment agent, and a known surface treatment agent can be used, such as a silane coupling agent, an organic titanium coupling agent, an organic zirconium coupling agent, or an organic aluminum coupling agent. The surface treatment agent may be used alone or in combination of two or more types. Among these, a silane coupling agent is preferred from the viewpoint of the affinity between the polymerizable monomer (A) and the inorganic filler (B) and availability.
[0039] The type of silane coupling agent is not particularly limited, but it is preferably a compound represented by the following general formula (4). [ka] (In the formula, R 4 is a hydrogen atom or a methyl group, R 5 is an oxygen atom, a sulfur atom, or -NR 8 - where R 8 is a hydrogen atom or an aliphatic group having 1 to 8 carbon atoms (which may be linear, branched, or cyclic), and R 6 is a hydrolyzable group, R 7 is a hydrocarbon group having 1 to 6 carbon atoms, p is an integer of 1 to 3, q is an integer of 1 to 13, and a plurality of R 6 and R 7 may be the same or different from each other.)
[0040] In the above general formula (4), R 4 is a hydrogen atom or a methyl group, and is preferably a methyl group. 5 is an oxygen atom, a sulfur atom, or -NR 8 -, and is preferably an oxygen atom. 8 is a hydrogen atom or an aliphatic group having 1 to 8 carbon atoms (which may be linear, branched, or cyclic), and R 8 The aliphatic group having 1 to 8 carbon atoms represented by the formula (I) may be either a saturated aliphatic group (such as an alkyl group or a cycloalkylene group (such as a cyclohexyl group)) or an unsaturated aliphatic group (such as an alkenyl group or an alkynyl group), and from the viewpoints of availability, ease of production, chemical stability, etc., it is preferably a saturated aliphatic group, and more preferably an alkyl group. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, an n-hexyl group, an n-heptyl group, a 2-methylhexyl group, and an n-octyl group. 8is preferably a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, more preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and even more preferably a hydrogen atom.
[0041] In the above general formula (4), R 6 Examples of the hydrolyzable group represented by the formula (I) include alkoxy groups such as methoxy, ethoxy, and butoxy; halogen atoms such as chlorine and bromine; and isocyanate groups. 6 If there are multiple R 6 may be the same or different. Among these, R 6 is preferably an alkoxy group, more preferably a methoxy group or an ethoxy group, and further preferably a methoxy group.
[0042] In the above general formula (4), R 7 Examples of the hydrocarbon group having 1 to 6 carbon atoms represented by the formula (1) include an alkyl group having 1 to 6 carbon atoms (which may be cyclic), an alkenyl group having 2 to 6 carbon atoms (which may be cyclic), and an alkynyl group having 2 to 6 carbon atoms. 7 If there are multiple R 7 may be the same or different from each other.
[0043] Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, an n-hexyl group, a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group.
[0044] Examples of the alkenyl group having 2 to 6 carbon atoms include a vinyl group, an allyl group, a 1-methylvinyl group, a 1-propenyl group, a butenyl group, a pentenyl group, a hexenyl group, a cyclopropenyl group, a cyclobutenyl group, a cyclopentenyl group, and a cyclohexenyl group.
[0045] Examples of the alkynyl group having 2 to 6 carbon atoms include ethynyl, 1-propynyl, 2-propynyl, 1-butynyl, 1-methyl-2-propynyl, 2-butynyl, 3-butynyl, 1-pentynyl, 1-ethyl-2-propynyl, 2-pentynyl, 3-pentynyl, 1-methyl-2-butynyl, 4-pentynyl, 1-methyl-3-butynyl, 2-methyl-3-butynyl, 1-hexynyl, 2-hexynyl, 1-ethyl-2-butynyl, 3-hexynyl, 1-methyl-2-pentynyl, 1-methyl-3-pentynyl, 4-methyl-1-pentynyl, 3-methyl-1-pentynyl, 5-hexynyl, and 1-ethyl-3-butynyl.
[0046] In the above general formula (4), p is an integer of 1 to 3, preferably 2 or 3, and more preferably 3. In addition, in the above general formula (4), q is an integer of 1 to 13, preferably an integer of 2 to 12, and more preferably an integer of 3 to 11.
[0047] Specific examples of the silane coupling agent represented by the above general formula (4) include, for example, methacryloyloxymethyltrimethoxysilane, 2-methacryloyloxyethyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 4-methacryloyloxybutyltrimethoxysilane, 5-methacryloyloxypentyltrimethoxysilane, 6-methacryloyloxyhexyltrimethoxysilane, 7-methacryloyloxyheptyltrimethoxysilane, 8-methacryloyloxyoctyltrimethoxysilane, Examples of the silane coupling agent include silane, 9-methacryloyloxynonyltrimethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 11-methacryloyloxyundecyltrimethoxysilane, 12-methacryloyloxydodecyltrimethoxysilane, 13-methacryloyloxytridecyltrimethoxysilane, 11-methacryloyloxyundecyldichloromethylsilane, 11-methacryloyloxyundecyltrichlorosilane, and 12-methacryloyloxydodecyldimethoxymethylsilane. The silane coupling agent may be used alone or in combination of two or more kinds. Among these, from the viewpoint of availability, 3-methacryloyloxypropyltrimethoxysilane is preferred, and from the viewpoint of further increasing the affinity between the polymerizable monomer (A) and the inorganic filler (B), 8-methacryloyloxyoctyltrimethoxysilane, 9-methacryloyloxynonyltrimethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, and 11-methacryloyloxyundecyltrimethoxysilane are preferred.
[0048] The surface treatment method is not particularly limited, and any known method can be applied.
[0049] There is no particular limit to the amount of the surface treatment agent used, but the amount of the surface treatment agent used can be, for example, 1 part by mass or more relative to 100 parts by mass of the filler before surface treatment, and the amount used is preferably 5 parts by mass or more, more preferably 6 parts by mass or more, even more preferably 8 parts by mass or more, particularly preferably 10 parts by mass or more, most preferably 20 parts by mass or more, and preferably 50 parts by mass or less, more preferably 45 parts by mass or less, and even more preferably 40 parts by mass or less. By using an amount equal to or more than the lower limit, the mechanical strength of the cured product obtained is more likely to be improved, and by using an amount equal to or less than the upper limit, the decrease in the mechanical strength of the cured product obtained due to excess surface treatment agent can be suppressed.
[0050] The content of the inorganic filler (B) in the dental curable composition of the present invention (the content of the inorganic filler (B) after the surface treatment in the case of surface treatment) is not particularly limited, but from the viewpoint of the operability of the obtained dental curable composition and the mechanical strength of the cured product, it is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 50% by mass or more, particularly preferably 65% by mass or more, and preferably 97% by mass or less, more preferably 96% by mass or less, even more preferably 95% by mass or less, and particularly preferably 90% by mass or less, based on the total mass of the dental curable composition. By the content of the inorganic filler (B) being equal to or more than the above lower limit, the mechanical strength of the cured product is improved, and the stickiness of the dental curable composition is more effectively suppressed, thereby improving the operability. In addition, by the content of the inorganic filler (B) being equal to or less than the above upper limit, it is possible to suppress the obtained dental curable composition from becoming excessively hard, thereby improving the operability. In addition, the content of the inorganic filler (B) in the dental curable composition of the present invention is, relative to 100 parts by mass of the total mass of the polymerizable monomer (A) and the inorganic filler (B), preferably 10 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 50 parts by mass or more, and particularly preferably 65 parts by mass or more, and is preferably 97 parts by mass or less, more preferably 96 parts by mass or less, even more preferably 95 parts by mass or less, and particularly preferably 90 parts by mass or less.
[0051] The dental curable composition of the present invention may contain an organic filler. Examples of the organic filler include acrylic polymers such as polymethyl methacrylate, polyethyl methacrylate, methyl methacrylate-ethyl methacrylate copolymer, crosslinked polymethyl methacrylate, crosslinked polyethyl methacrylate, and polyamide; polyvinyl chloride, polystyrene, chloroprene rubber, nitrile rubber, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, acrylonitrile-styrene copolymer, and acrylonitrile-styrene-butadiene copolymer, and these can be used alone or as a mixture of two or more. The shape of the organic filler is not particularly limited, and the particle size of the organic filler can be appropriately selected and used. From the viewpoint of the handleability and mechanical strength of the obtained composition, the average particle size of the organic filler is preferably 0.001 to 50 μm, and more preferably 0.001 to 10 μm. The method for measuring the average particle size of the organic filler includes the same method as that for the average particle size of the inorganic filler (B).
[0052] [Polymerization initiator (C)] The dental curable composition of the present invention contains a polymerization initiator (C). The polymerization initiator (C) can be selected from polymerization initiators used in general industry, and among them, polymerization initiators used for dental applications are preferably used. In particular, photopolymerization initiators and chemical polymerization initiators are preferably used. The polymerization initiator (C) may be used alone or in appropriate combination of two or more.
[0053] Examples of the photopolymerization initiator include (bis)acylphosphine oxides, ketals, α-diketones, and coumarin compounds.
[0054] Among the (bis)acylphosphine oxides, examples of the acylphosphine oxides include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide, benzoyldi(2,6-dimethylphenyl)phosphonate, and salts thereof (such as sodium salts, potassium salts, and ammonium salts). Examples of the bisacylphosphine oxides include bis(2,6-dichlorobenzoyl)phenylphosphine oxide, bis(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide, and salts thereof (such as sodium salts, potassium salts, and ammonium salts).
[0055] Among these (bis)acylphosphine oxides, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoylphenylphosphine oxide sodium salt are particularly preferred.
[0056] Examples of the ketals include benzyl dimethyl ketal and benzyl diethyl ketal.
[0057] Examples of α-diketones include diacetyl, benzil, camphorquinone, 2,3-pentadione, 2,3-octadione, 9,10-phenanthrenequinone, 4,4′-oxybenzil, acenaphthenequinone, etc. Among these, camphorquinone is particularly preferred because it has a maximum absorption wavelength in the visible light region.
[0058] Examples of the coumarin compounds include 3,3'-carbonylbis(7-diethylaminocoumarin), 3-(4-methoxybenzoyl)coumarin, 3-thienoylcoumarin, 3-benzoyl-5,7-dimethoxycoumarin, 3-benzoyl-7-methoxycoumarin, 3-benzoyl-6-methoxycoumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoylcoumarin, 7-methoxy-3-(p-nitrobenzoyl)coumarin, 3-(p-nitrobenzoyl)coumarin, 3,5-carbonylbis(7-methoxycoumarin), 3-benzoyl-6-bromo Coumarin, 3,3'-carbonylbiscoumarin, 3-benzoyl-7-dimethylaminocoumarin, 3-benzoylbenzo[f]coumarin, 3-carboxycoumarin, 3-carboxy-7-methoxycoumarin, 3-ethoxycarbonyl-6-methoxycoumarin, 3-ethoxycarbonyl-8-methoxycoumarin, 3-acetylbenzo[f]coumarin, 3-benzoyl-6-nitrocoumarin, 3-benzoyl-7-diethylaminocoumarin, 7-dimethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3-(4-methoxybenzoyl)coumarin )coumarin, 7-diethylamino-3-(4-diethylamino)coumarin, 7-methoxy-3-(4-methoxybenzoyl)coumarin, 3-(4-nitrobenzoyl)benzo[f]coumarin, 3-(4-ethoxycinnamoyl)-7-methoxycoumarin, 3-(4-dimethylaminocinnamoyl)coumarin, 3-(4-diphenylaminocinnamoyl)coumarin, 3-[(3-dimethylbenzothiazol-2-ylidene)acetyl]coumarin, 3-[(1-methylnaphtho[1,2-d]thiazol-2-ylidene)acetyl]coumarin, 3,3'-carbo nylbis(6-methoxycoumarin), 3,3'-carbonylbis(7-acetoxycoumarin), 3,3'-carbonylbis(7-dimethylaminocoumarin), 3-(2-benzothiazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dibutylamino)coumarin, 3-(2-benzimidazolyl)-7-(diethylamino)coumarin, 3-(2-benzothiazolyl)-7-(dioctylamino)coumarin, 3-acetyl-7-(dimethylamino)coumarin, 3,3'-carbonylbis(7-dibutylamino)coumarin, 3,Examples of the compounds include those described in JP-A-9-3109 and JP-A-10-245525, such as 3'-carbonyl-7-diethylaminocoumarin-7'-bis(butoxyethyl)aminocoumarin, 10-[3-[4-(dimethylamino)phenyl]-1-oxo-2-propenyl]-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one, and 10-(2-benzothiazolyl)-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one.
[0059] Among the above-mentioned coumarin compounds, 3,3'-carbonylbis(7-diethylaminocoumarin) and 3,3'-carbonylbis(7-dibutylaminocoumarin) are particularly preferred.
[0060] By using at least one selected from the group consisting of (bis)acylphosphine oxides, α-diketones, and coumarin compounds among the photopolymerization initiators, it is possible to obtain a dental curable composition that has excellent photocurability in the visible and near ultraviolet regions and exhibits sufficient photocurability using any light source, including a halogen lamp, a light-emitting diode (LED), and a xenon lamp.
[0061] As the chemical polymerization initiator, an organic peroxide is preferably used. The organic peroxide used as the above-mentioned chemical polymerization initiator is not particularly limited, and any known organic peroxide can be used. Representative organic peroxides include ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, and peroxydicarbonates.
[0062] Examples of the ketone peroxide include methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, methylcyclohexanone peroxide, and cyclohexanone peroxide.
[0063] Examples of hydroperoxides include 2,5-dimethylhexane-2,5-dihydroperoxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide.
[0064] Examples of the diacyl peroxide include acetyl peroxide, isobutyryl peroxide, benzoyl peroxide, decanoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide.
[0065] Examples of dialkyl peroxides include di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 1,3-bis(t-butylperoxyisopropyl)benzene, and 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne.
[0066] Examples of peroxyketals include 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, and 4,4-bis(t-butylperoxy)valeric acid-n-butyl ester.
[0067] Examples of peroxyesters include α-cumyl peroxyneodecanoate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, 2,2,4-trimethylpentyl peroxy-2-ethylhexanoate, t-amyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, di-t-butyl peroxyisophthalate, di-t-butyl peroxyhexahydroterephthalate, t-butyl peroxy-3,3,5-trimethylhexanoate, t-butyl peroxyacetate, t-butyl peroxybenzoate, and t-butyl peroxymaleic acid.
[0068] Examples of peroxydicarbonates include di-3-methoxyperoxydicarbonate, di(2-ethylhexyl)peroxydicarbonate, bis(4-t-butylcyclohexyl)peroxydicarbonate, diisopropylperoxydicarbonate, di-n-propylperoxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, and diallylperoxydicarbonate.
[0069] Among the organic peroxides, diacyl peroxides are preferably used from the viewpoint of the overall balance of safety, storage stability, and radical generating ability, and among them, benzoyl peroxide is particularly preferably used.
[0070] The content of the polymerization initiator (C) in the dental curable composition of the present invention is not particularly limited, but from the viewpoint of the curability of the obtained dental curable composition, it is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, even more preferably 0.02 parts by mass or more, and particularly preferably 0.1 parts by mass or more, relative to the total mass 100 parts by mass of the polymerizable monomer (A), since precipitation may occur from the dental curable composition if the content of the polymerization initiator (C) is too high, the content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, particularly preferably 10 parts by mass or less, and may be 5 parts by mass or less, 2 parts by mass or less, relative to the total mass 100 parts by mass of the polymerizable monomer (A).
[0071] [Fluorescent agent (D)] The dental curable composition of the present invention includes a fluorescent agent (D). The fluorescent agent (D) includes a 9-11-membered benzo-fused heterocycle-containing compound (excluding benzimidazole compounds) containing two or more heteroatoms. Examples of the heteroatom include an oxygen atom, a sulfur atom, and a nitrogen atom, and oxygen and nitrogen atoms are preferred. Of the two or more heteroatoms contained in the benzo-fused heterocycle-containing compound, at least one is preferably a nitrogen atom. The benzo-fused heterocycle-containing compound is preferably a fluorescent agent (D-1) (hereinafter, also simply referred to as "fluorescent agent (D-1)") which is a benzo-fused heterocycle-containing compound containing two heteroatoms. The benzo-fused heterocycle-containing compound has a fused ring in which a heterocycle containing two heteroatoms and a benzene ring are condensed. Examples of the fluorescent agent (D-1) include a compound containing a benzodiazinon skeleton or a compound containing a benzoxazinone skeleton. Examples of the compound containing a benzodiazinon skeleton include a compound containing a quinazolinone skeleton (D-1a), a compound containing a cinnolinone skeleton (D-1b), a compound containing a phthalazinone skeleton (D-1c), and a compound containing a quinoxalinone skeleton (D-1d), and the quinazolinone skeleton (D-1a) is preferred. By including the fluorescent agent (D-1), the dental hardenable composition has sufficient fluorescence, is highly aesthetic, and has excellent color resistance in the oral cavity, under accelerated heating conditions, and under xenon lamp light exposure conditions, and is suitable for dental composite resins and dental mill blanks, etc., in which the fluorescence is not deactivated even under such conditions, and the hardened product thereof. The reason why the dental hardenable composition of the present invention and the hardened product thereof exhibit the above-mentioned excellent effects is not necessarily clear, but it is thought to be due to the high stability of the 9- to 11-membered benzo-fused heterocyclic skeleton containing two or more heteroatoms, such as the benzodiazinon skeleton or the benzoxazinone skeleton.
[0072] The fluorescent agent (D-1) is preferably a compound containing a benzodiazinone skeleton (particularly preferably a quinazolinone skeleton) or a compound containing at least one of benzoxazinone skeletons, and more preferably a compound (D-1a) containing a quinazolinone skeleton. The fluorescent agent (D-1) may have one or more benzodiazinone skeletons (particularly preferably a quinazolinone skeleton) or benzoxazinone skeletons.
[0073] The benzodiazinon skeleton is represented by the following general formula (5). [ka] Here, in the general formula (5), X represents a 6-membered heterocyclic ring containing two nitrogen atoms, and the 6-membered heterocyclic ring has at least one oxo group (=O) and may have a substituent. It is preferable that X is an aromatic heterocyclic ring and contains one -NH- in the ring. The number of oxo groups is not particularly limited, and is 1 or 2, and 1 is preferable. Specifically, X represents any one of the moieties of the following formulae (X-1) to (X-5), and formulae (X-3) and (X-4) are preferable, and formula (X-3) is more preferable. [ka] [ka] [ka] [ka] [ka]
[0074] The benzoxazinone skeleton is represented by the following general formula (6). [ka] Here, in the general formula (6), Y represents a 6-membered heterocyclic ring containing one nitrogen atom and one oxygen atom, and the 6-membered heterocyclic ring has at least one oxo group and may have a substituent. Y is preferably an aromatic heterocyclic ring. The number of oxo groups is not particularly limited, and is 1 or 2, and 1 is preferred. Specifically, Y represents any one of the moieties of the following formulae (Y-1) to (Y-6), and formulae (Y-5) and (Y-6) are preferred. [ka] [ka] [ka] [ka] [ka] [ka]
[0075] The benzodiazinone skeleton (particularly preferably the quinazolinone skeleton) and the benzoxazinone skeleton may or may not have a substituent.
[0076] Examples of the substituent include a hydroxyl group, a thiol group, a nitro group, a halogen atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group such as a vinyl group or an allyl group, an alkoxy group having 1 to 10 carbon atoms, an aromatic group such as a phenyl group, a naphthyl group or a styryl group, a halogenated alkyl group having 1 to 10 carbon atoms substituted with a halogen atom, an acyl group such as an acetyl group, an amino group, an alkylamino group such as a methylamino group, a dialkylamino group such as a dimethylamino group, an aminoalkyl group such as an aminoethyl group, a carboxy group, an alkoxycarbonyl group such as a methoxycarbonyl group, an alkoxycarbonylalkyl group such as a methoxycarbonylmethyl group, an alkyloxyalkyl group such as a methyloxymethyl group, and an alkyl group such as a methylthiomethyl group. Examples of the substituents include thioalkyl groups, aminoalkylaminoalkyl groups such as aminomethylaminomethyl groups, alkylcarbonyloxy groups such as methylcarbonyloxy groups, arylalkoxyalkoxyalkyl groups such as benzyloxyethoxyethyl groups, hydroxyalkoxyalkyl groups such as hydroxyethoxymethyl groups, arylalkoxyalkyl groups such as benzyloxymethyl groups, quaternary ammonio groups such as trimethylammonio groups, cycloalkyl groups such as cyclopropyl groups, alkoxycarbonyl groups such as tert-butoxycarbonyl groups, substituted sulfonyl groups such as p-toluenesulfonyl groups, substituted sulfonamide groups such as benzenesulfonamide groups, aryloyl groups such as benzoyl groups, and oxygen atoms (=O). The number of the substituents may be 1 to 10, 1 to 6, or 1 to 3. The substituents may be combined, and for example, the substituent may be further substituted or unsubstituted by another of the substituents.
[0077] Among the fluorescent agents (D-1), compounds having a moiety represented by the following general formula (1) or (2) are preferred. [ka] [ka] (R in general formulas (1) and (2) 1is an oxygen atom or -NH-, R 2 represents an aromatic group which may have a substituent.
[0078] R 2 Examples of the aromatic group represented by the formula (I) include aryl groups such as a phenyl group, a biphenylyl group, a terphenylyl group, a styryl group, a naphthyl group, an anthryl group, an acenaphthenyl group, a fluorenyl group, a phenanthryl group, and an indenyl group; aralkyl groups such as a benzyl group, a phenethyl group, a 1-phenylethyl group, a 2-phenylpropyl group, a 3-phenylpropyl group, a phenylbutyl group, a 1-methyl-3-phenylpropyl group, a naphthylmethyl group, a naphthylethyl group, a naphthylpropyl group, and a naphthylbutyl group; and heteroaromatic rings such as a pyrenyl group, a pyrimidyl group, a furanyl group, a pyronyl group, a thienyl group, a quinolyl group, a benzofuranyl group, a benzothiophenyl group, an indolyl group, a carbazolyl group, a carbolyl group, a benzoxazolyl group, a quinoxalyl group, a benzimidazolyl group, a pyrazolyl group, a dibenzofuranyl group, and a dibenzothiophenyl group. Among these, from the viewpoints of fluorescence and durability, a phenyl group, a naphthyl group, and a styryl group are preferred.
[0079] R 2 The aromatic group represented by may or may not have a substituent. Examples of the substituent include the substituents described above as the substituents of the benzodiazinone skeleton and the benzoxazinone skeleton. Among the substituents, from the viewpoint of fluorescence and durability, a hydroxyl group, a halogen atom, an alkyl group having 1 to 3 carbon atoms, a halogenated alkyl group having 1 to 3 carbon atoms substituted with a halogen atom, a dimethylamino group, a carboxy group, and a benzenesulfonamide group are preferred. The number of the substituents may be 1 to 20, 1 to 10, 1 to 6, or 1 to 3. The substituents may be combined, and for example, the substituent may be further substituted by another of the substituents, or may not be substituted.
[0080] Among the fluorescent agents (D-1), from the viewpoints of fluorescence and durability, 2-(2-hydroxyphenyl)-4(1H)-quinazolinone, 2-(2-hydroxyphenyl)-4H-3,1-benzoxazin-4-one, N-[2-(4(1H)-quinazolinon-2-yl)phenyl]benzenesulfonamide, N-[2-(4-oxo-1,3-benzoxazin-2-yl)phenyl]benzenesulfonamide, 7-dimethylamino-3-[2-[4-(trifluoromethyl)phenyl]ethenyl]-2H-1,4-benzoxazin-2-one, 7-Dimethylamino-3-[2-[2,3,4,5,6-pentafluorophenyl]ethenyl]-2H-1,4-benzoxazin-2-one, 7-dimethylamino-3-[2-[2,4-bis(trifluoromethyl)phenyl]ethenyl]-2H-1,4-benzoxazin-2-one, is preferred, 2-(2-hydroxyphenyl)-4(1H)-quinazolinone, N-[2-(4-oxo-1,3-benzoxazin-2-yl)phenyl]benzenesulfonamide, is more preferred.
[0081] The content of the fluorescent agent (D-1) in the dental curable composition of the present invention is not particularly limited, but in order for the resulting dental curable composition to exhibit sufficient fluorescence, the content is preferably 0.0001 parts by mass or more, more preferably 0.0002 parts by mass or more, even more preferably 0.0005 parts by mass or more, and particularly preferably 0.001 parts by mass or more, relative to 100 parts by mass of the total mass of the polymerizable monomer (A) and the inorganic filler (B), and the content is preferably 0.0005 parts by mass or more, more preferably 0.001 parts by mass or more, even more preferably 0.002 parts by mass or more, and particularly preferably 0.005 parts by mass or more, relative to 100 parts by mass of the total mass of the polymerizable monomer (A). In addition, if the content of the fluorescent agent (D-1) is too high, the aesthetics of the dental hardenable composition may deteriorate. Therefore, the content is preferably 3 parts by mass or less, more preferably 1 part by mass or less, even more preferably 0.5 parts by mass or less, and particularly preferably 0.1 parts by mass or less, relative to 100 parts by mass of the total mass of the polymerizable monomer (A) and the inorganic filler (B), and is preferably 5 parts by mass or less, more preferably 1 part by mass or less, even more preferably 0.5 parts by mass or less, and particularly preferably 0.2 parts by mass or less, relative to 100 parts by mass of the total mass of the polymerizable monomer (A). The fluorescent agent (D-1) may be used alone or in combination of two or more kinds. By using two or more kinds in combination, the fluorescent color of the hardened product of the dental hardenable composition of the present invention can be adjusted arbitrarily depending on the blending ratio, and the fluorescence closer to that of natural teeth can be reproduced, and a dental hardenable composition with high aesthetics can be provided.
[0082] The dental curable composition of the present invention preferably further contains, as the fluorescent agent (D), a fluorescent agent (D-2) which is a benzo-fused heterocyclic 5-membered ring-containing compound containing one nitrogen atom and one oxygen atom, in addition to the fluorescent agent (D-1). The benzo-fused heterocyclic 5-membered ring-containing compound has a condensed ring in which a heterocyclic 5-membered ring containing one nitrogen atom and one oxygen atom is condensed with a benzene ring. Examples of the fluorescent agent (D-2) include a fluorescent agent (D-2a) (hereinafter, also simply referred to as "fluorescent agent (D-2a)") which is a compound containing a benzoxazole skeleton, and a fluorescent agent (D-2b) which is a compound containing a benzoisoxazole skeleton, and the fluorescent agent (D-2a) which is a compound containing a benzoxazole skeleton is particularly preferred. By using the fluorescent agent (D-1) and the fluorescent agent (D-2) in combination, the fluorescent color of the cured product of the dental hardenable composition of the present invention can be adjusted arbitrarily by changing the mixing ratio thereof, and fluorescence closer to that of natural teeth can be reproduced. Furthermore, the dental hardenable composition has excellent color fastness and fluorescence durability, so that a highly aesthetic dental hardenable composition can be provided.
[0083] The fluorescent agent (D-2a) means a compound containing a benzoxazole skeleton represented by the following formula (7). The fluorescent agent (D-2a) may have a plurality of benzoxazole skeletons. The benzoxazole skeleton may or may not have a substituent. Examples of the substituent include the substituents described as the substituents of the quinazolinone skeleton and the benzoxazinone skeleton. Among the substituents, a hydroxyl group, a halogen atom, and an alkyl group having 1 to 3 carbon atoms are preferable from the viewpoint of fluorescence and durability. The number of the substituents may be 1 to 20, 1 to 10, 1 to 6, or 1 to 3. The substituent may or may not have a further substituent. [ka]
[0084] Among the fluorescent agents (D-2a), compounds having a moiety represented by the following general formula (3) are preferred from the viewpoints of fluorescent color and durability. [ka] (wherein, in general formula (3), R 3 represents an aromatic group which may have a substituent, or a vinylene group which may have a substituent.
[0085] R 3 The aromatic group represented by is, for example, R 2 Among them, a phenylene group, a naphthylene group, and a thienylene group are preferable.
[0086] The compound represented by the general formula (3) may or may not have a substituent. Examples of the substituent include the same ones as those of the benzoxazole skeleton.
[0087] Among the fluorescent agents (D-2a) of compounds containing the benzoxazole skeleton, from the viewpoints of fluorescence and durability, 1,4-bis(2-benzoxazolyl)naphthalene, 4,4'-bis(2-benzoxazolyl)stilbene, 1,2-bis(5-methylbenzoxazol-2-yl)ethene, 4,4'-bis(5-methyl-2-benzoxazolyl)stilbene, 4-(2-benzoxazolyl)-4'-(5-methyl-2-benzoxazolyl)stilbene, 2,5-bis(benzoxazol-2-yl)thiophene, 2,5-bis(5-tert-butyl-2-benzoxazolyl)thiophene, is preferred.
[0088] The content of the fluorescent agent (D-2) in the dental curable composition of the present invention is not particularly limited, but in order for the dental curable composition obtained to show sufficient fluorescence, it is preferably 0.0001 parts by mass or more, more preferably 0.0002 parts by mass or more, even more preferably 0.0005 parts by mass or more, and particularly preferably 0.001 parts by mass or more, relative to the total mass 100 parts by mass of the polymerizable monomer (A) and the inorganic filler (B), in order for the dental curable composition obtained to show sufficient fluorescence, the content of the fluorescent agent (D-2) is preferably 0.0005 parts by mass or more, more preferably 0.001 parts by mass or more, even more preferably 0.002 parts by mass or more, and particularly preferably 0.005 parts by mass or more, relative to the total mass 100 parts by mass of the polymerizable monomer (A). In addition, if the content of the fluorescent agent (D-2) is too high, the aesthetics of the dental hardenable composition may deteriorate, so the content of the fluorescent agent (D-2) is preferably 3 parts by mass or less, more preferably 1 part by mass or less, even more preferably 0.5 parts by mass or less, and particularly preferably 0.1 parts by mass or less, relative to 100 parts by mass of the total of the polymerizable monomer (A) and the inorganic filler (B). In addition, if the content of the fluorescent agent (D-2) is too high, the aesthetics of the dental hardenable composition may deteriorate, so the content of the fluorescent agent (D-2) is preferably 5 parts by mass or less, more preferably 1 part by mass or less, even more preferably 0.5 parts by mass or less, and particularly preferably 0.2 parts by mass or less, relative to 100 parts by mass of the total of the polymerizable monomer (A). The fluorescent agent (D-2) may be used alone or in combination of two or more kinds. An embodiment of the present invention includes a dental curable composition comprising a polymerizable monomer (A), an inorganic filler (B), a polymerization initiator (C), and a fluorescent agent (D), wherein the fluorescent agent (D) comprises a 9- to 11-membered benzo-fused heterocycle-containing compound having two or more heteroatoms (excluding benzimidazole compounds), and the 9- to 11-membered benzo-fused heterocycle-containing compound having two or more heteroatoms does not comprise a fluorescent agent (D-1) but comprises a fluorescent agent (D-2).
[0089] The dental hardenable composition of the present invention may contain a fluorescent agent (D-3) containing a phthalate ester within the range in which the effects of the present invention are achieved. The fluorescent agent (D-3) containing a phthalate ester is distinguished from the fluorescent agents (D-1) and (D-2). The fluorescent agent (D-3) containing a phthalate ester is represented by the following general formula (8). [ka] (In the formula, R 10 and R 11 are each independently an alkyl group; R 12 is a hydrogen atom, an amino group, or a hydroxyl group, and R 13 is an amino group or a hydroxyl group.
[0090] The alkyl group is preferably one having 1 to 3 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, or an i-propyl group, and more preferably one having 1 to 2 carbon atoms.
[0091] The content of the fluorescent agent (D-3) in the dental curable composition of the present invention may cause a color change (yellowing) of the dental curable composition, so it is preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, even more preferably 0.01 parts by mass or less, and particularly preferably not contained, relative to 100 parts by mass of the total of the polymerizable monomer (A) and the inorganic filler (B). The content of the fluorescent agent (D-3) may cause a color change (yellowing) of the dental curable composition, so it is preferably 0.1 parts by mass or less, more preferably 0.01 parts by mass or less, even more preferably 0.001 parts by mass or less, and particularly preferably not contained. The fluorescent agent (D-3) may be used alone or in combination of two or more kinds. A preferred embodiment of the present invention is a dental curable composition in which the fluorescent agent (D) does not contain the fluorescent agent (D-3).
[0092] The fluorescent agent (D) in the dental hardenable composition of the present invention may further contain a fluorescent agent (D-4) other than the fluorescent agents (D-1), (D-2), and (D-3).
[0093] The fluorescent agent (D-4) can be selected from fluorescent agents used in general industry, and among them, fluorescent agents used in dental applications are preferably used. Such fluorescent agents (D-4) are roughly classified into organic fluorescent agents and inorganic fluorescent agents. The fluorescent agent (D-4) may be used alone or in combination of two or more.
[0094] Examples of the organic fluorescent agent include coumarin-based fluorescent agents, naphthalimide-based fluorescent agents, xanthene-based fluorescent agents, thioxanthene-based fluorescent agents, naphtholactam-based fluorescent agents, thiazine-based fluorescent agents, oxazole-based fluorescent agents, furan-based fluorescent agents, benzofuran-based fluorescent agents, pyrazoline-based fluorescent agents, stilbene-based fluorescent agents, distyrylbenzene-based fluorescent agents, distyrylbiphenyl-based fluorescent agents, benzimidazole compounds, 1,3,5-triazin-2-yl derivatives, arylbenzoguanamine-based fluorescent agents, and polycyclic aromatic hydrocarbon-based fluorescent agents.
[0095] Examples of the inorganic fluorescent agent include Y2SiO5:Ce, Y2SiO5:Tb, (Y,Gd,Eu)BO3, Y2O3:Eu, YAG:Ce, ZnGa2O4:Zn, and BaMgAl 10 O 17 :Eu,BaMgAl 10 O 17 :Eu, (SrCaBaMg)5(PO4)3Cl:Eu, Zn2SiO4:Mn, BaMg2Al 16 O 27 :Eu, BaMg2Al 16 O 27 :Eu,Mn,BaMg2Al 16 O 27 :Mn, LaPO4:Ce, LaPO4:Tb, LaPO4:Ce,Tb, Y3Al5O 12 Among them, Y2SiO5:Ce is preferable from the viewpoint of fluorescent color.
[0096] [Polymerization accelerator (E)] The dental curable composition of the present invention may further contain a polymerization accelerator (E). Examples of the polymerization accelerator include amines, sulfinic acid and its salts, barbituric acid derivatives, borate compounds, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, thiol compounds, sulfites, hydrogen sulfites, and thiourea compounds. The polymerization accelerator (E) may be used alone or in combination of two or more. In a preferred embodiment, the dental curable composition includes a polymerization initiator (C) containing a photopolymerization initiator and further containing a polymerization accelerator (E), and the polymerization accelerator (E) is a tertiary amine. The tertiary amine is preferably a tertiary aromatic amine. The dental curable composition of the preferred embodiment is more suitable as a dental composite resin.
[0097] Amines are divided into aliphatic amines and aromatic amines. Examples of aliphatic amines include primary aliphatic amines such as n-butylamine, n-hexylamine, and n-octylamine; secondary aliphatic amines such as diisopropylamine, dibutylamine, and N-methylethanolamine; and tertiary aliphatic amines such as N-methyldiethanolamine, N-ethyldiethanolamine, Nn-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, triethanolamine, trimethylamine, triethylamine, and tributylamine. Among them, from the viewpoint of the hardening property and storage stability of dental hardenable composition, tertiary aliphatic amines are preferred, and N-methyldiethanolamine and triethanolamine are more preferably used.
[0098] Examples of aromatic amines include N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-bis(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-t-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-isopropylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-t-butylaniline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, and N,N-dimethyl-m-toluidine. dimethylaniline, N,N-diethyl-p-toluidine, N,N-dimethyl-3,5-dimethylaniline, N,N-dimethyl-3,4-dimethylaniline, N,N-dimethyl-4-ethylaniline, N,N-dimethyl-4-isopropylaniline, N,N-dimethyl-4-t-butylaniline, N,N-dimethyl-3,5-di-t-butylaniline, 4-(N,N-dimethylamino)ethyl benzoate, 4-(N,N-dimethylamino)methyl benzoate, 4-(N,N-dimethylamino)benzoic acid 2-butoxyethyl, 4-(N,N-dimethylamino)benzoic acid 2-(methacryloyloxy)ethyl, 4-(N,N-dimethylamino)benzophenone, 4-(N,N-dimethylamino)butyl benzoate, and the like. Among these, from the viewpoint of imparting excellent hardenability to the dental hardenable composition, at least one selected from the group consisting of N,N-bis(2-hydroxyethyl)-p-toluidine, ethyl 4-(N,N-dimethylamino)benzoate, 2-butoxyethyl 4-(N,N-dimethylamino)benzoate, and 4-(N,N-dimethylamino)benzophenone is preferably used.
[0099] Examples of sulfinic acids and salts thereof include p-toluenesulfinic acid, sodium p-toluenesulfinate, potassium p-toluenesulfinate, lithium p-toluenesulfinate, calcium p-toluenesulfinate, benzenesulfinic acid, sodium benzenesulfinate, potassium benzenesulfinate, lithium benzenesulfinate, calcium benzenesulfinate, 2,4,6-trimethylbenzenesulfinic acid, sodium 2,4,6-trimethylbenzenesulfinate, potassium 2,4,6-trimethylbenzenesulfinate, lithium 2,4,6-trimethylbenzenesulfinate, calcium 2,4,6-trimethylbenzenesulfinate, 2,4,6-triethylbenzenesulfinic acid, Examples of the sulfinic acid salt include sodium 2,4,6-triethylbenzenesulfinate, potassium 2,4,6-triethylbenzenesulfinate, lithium 2,4,6-triethylbenzenesulfinate, calcium 2,4,6-triethylbenzenesulfinate, 2,4,6-triisopropylbenzenesulfinic acid, sodium 2,4,6-triisopropylbenzenesulfinate, potassium 2,4,6-triisopropylbenzenesulfinate, lithium 2,4,6-triisopropylbenzenesulfinate, and calcium 2,4,6-triisopropylbenzenesulfinate. Of these, sodium benzenesulfinate, sodium p-toluenesulfinate, and sodium 2,4,6-triisopropylbenzenesulfinate are particularly preferred.
[0100] Barbituric acid derivatives include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-5-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethyl-5-cyclopentylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-1-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 5-methylbarbituric acid, 5-propylbarbituric acid, 1, Examples of the barbituric acids include 5-diethylbarbituric acid, 1-ethyl-5-methylbarbituric acid, 1-ethyl-5-isobutylbarbituric acid, 1,3-diethyl-5-butylbarbituric acid, 1-cyclohexyl-5-methylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-cyclohexyl-5-octylbarbituric acid, 1-cyclohexyl-5-hexylbarbituric acid, 5-butyl-1-cyclohexylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, and thiobarbituric acids, as well as salts thereof (particularly preferred are salts of alkali metals or alkaline earth metals). Examples of the salts of the barbituric acids include sodium 5-butylbarbiturate, sodium 1,3,5-trimethylbarbiturate, and sodium 1-cyclohexyl-5-ethylbarbiturate.
[0101] Particularly suitable barbituric acid derivatives include 5-butylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, and the sodium salts of these barbituric acids.
[0102] The borate compound is preferably an aryl borate compound. Examples of the aryl borate compound include borate compounds having 1 to 4 aryl groups in one molecule. Among the aryl borate compounds, from the viewpoint of storage stability, borate compounds having 3 or 4 aryl groups in one molecule are preferred. Examples of the borate compound having 3 aryl groups in one molecule include monoalkyltriphenylboron, monoalkyltri(p-chlorophenyl)boron, monoalkyltri(p-fluorophenyl)boron, monoalkyltri[3,5-bis(trifluoromethyl)phenyl]boron, monoalkyltri[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, monoalkyltri(p-nitrophenyl)boron, monoalkyltri(m-nitrophenyl)boron, monoalkyltri(p-butylphenyl)boron, monoalkyltri(m-butylphenyl)boron, monoalkyltri( Examples of the alkyl group include monoalkyltri(m-butyloxyphenyl)boron, monoalkyltri(p-octyloxyphenyl)boron, monoalkyltri(m-octyloxyphenyl)boron (the alkyl group in each of the above examples is an n-butyl group, an n-octyl group, an n-dodecyl group, etc.), and salts thereof (sodium salt, lithium salt, potassium salt, magnesium salt, tetrabutylammonium salt, tetramethylammonium salt, tetraethylammonium salt, methylpyridinium salt, ethylpyridinium salt, butylpyridinium salt, methylquinolinium salt, ethylquinolinium salt, butylquinolinium salt, etc.).
[0103] Examples of borate compounds having four aryl groups in one molecule include tetraphenylboron, tetrakis(p-chlorophenyl)boron, tetrakis(p-fluorophenyl)boron, tetrakis[3,5-bis(trifluoromethyl)phenyl]boron, tetrakis[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, tetrakis(p-nitrophenyl)boron, tetrakis(m-nitrophenyl)boron, tetrakis(p-butylphenyl)boron, tetrakis(m-butylphenyl)boron, tetrakis(p-butyloxyphenyl)boron, tetrakis(m-butyloxyphenyl)boron, tetrakis(p-octyloxyphenyl)boron, and tetrakis(m-octyloxyphenyl)boron.
[0046] Examples of suitable aryloxyphenyls include (p-nitrophenyl)triphenylboron, (m-butyloxyphenyl)triphenylboron, (p-butyloxyphenyl)triphenylboron, (m-octyloxyphenyl)triphenylboron, (p-octyloxyphenyl)triphenylboron, and salts thereof (sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, butylquinolinium salts, etc.).
[0104] Examples of the triazine compound include 2,4,6-tris(trichloromethyl)-s-triazine, 2,4,6-tris(tribromomethyl)-s-triazine, 2-methyl-4,6-bis(trichloromethyl)-s-triazine, 2-methyl-4,6-bis(tribromomethyl)-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(p-methylthiophenyl)-4,6-bis(trichloromethyl)-s-triazine. , 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(2,4-dichlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-bromophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-n-propyl-4,6-bis(trichloromethyl)-s-triazine, 2-(α,α,β-trichloroethyl)-4,6-bis(trichloromethyl)-s-triazine, 2-styryl-4,6-bis s-triazine, 2-[2-(p-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(o-methoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(p-butoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(3,4-dimethoxyphenyl)ethenyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(3,4,5-trimethoxyphenyl)ethenyl]-4, 6-bis(trichloromethyl)-s-triazine, 2-(1-naphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-biphenylyl)-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N,N-bis(2-hydroxyethyl)amino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N-hydroxyethyl-N-ethylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N-hydroxyethyl-N-methylamino}ethoxy]-4,Examples include 6-bis(trichloromethyl)-s-triazine and 2-[2-{N,N-diallylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine.
[0105] Among the above-listed triazine compounds, 2,4,6-tris(trichloromethyl)-s-triazine is particularly preferred in terms of polymerization activity, and 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(4-biphenylyl)-4,6-bis(trichloromethyl)-s-triazine are particularly preferred in terms of storage stability. The above-listed triazine compounds may be used alone or in combination of two or more.
[0106] As the copper compound, for example, copper acetylacetonate, copper (II) acetate, copper oleate, copper (II) chloride, copper (II) bromide, etc. are suitably used.
[0107] Examples of the tin compound include di-n-butyltin dimaleate, di-n-octyltin dimaleate, di-n-octyltin dilaurate, di-n-butyltin dilaurate, etc. The tin compound is preferably di-n-octyltin dilaurate or di-n-butyltin dilaurate.
[0108] The vanadium compound is preferably a tetravalent and / or pentavalent vanadium compound. Examples of the tetravalent and / or pentavalent vanadium compound include compounds described in JP-A-2003-96122, such as divanadium(IV) tetroxide, vanadium oxide acetylacetonate(IV), vanadyl oxalate(IV), vanadyl sulfate(IV), oxo-bis(1-phenyl-1,3-butanedionato)vanadium(IV), bis(maltolato)oxo-vanadium(IV), vanadium pentoxide(V), sodium metavanadate(V), and ammonium metavanadate(V).
[0109] As the halogen compound, for example, dilauryl dimethyl ammonium chloride, lauryl dimethyl benzyl ammonium chloride, benzyl trimethyl ammonium chloride, tetramethyl ammonium chloride, benzyl dimethyl cetyl ammonium chloride, dilauryl dimethyl ammonium bromide, etc. are suitably used.
[0110] Examples of the aldehydes include terephthalaldehyde and benzaldehyde derivatives. Examples of the benzaldehyde derivatives include dimethylaminobenzaldehyde, p-methoxybenzaldehyde, p-ethoxybenzaldehyde, pn-octyloxybenzaldehyde, etc. Among them, pn-octyloxybenzaldehyde is preferably used from the viewpoint of curability.
[0111] Examples of the thiol compound include 3-mercaptopropyltrimethoxysilane, 2-mercaptobenzoxazole, decanethiol, and thiobenzoic acid.
[0112] Examples of sulfites include sodium sulfite, potassium sulfite, calcium sulfite, and ammonium sulfite.
[0113] Examples of hydrogen sulfites include sodium hydrogen sulfite and potassium hydrogen sulfite.
[0114] Examples of the thiourea compound include 1-(2-pyridyl)-2-thiourea, thiourea, methylthiourea, ethylthiourea, N,N'-dimethylthiourea, N,N'-diethylthiourea, N,N'-di-n-propylthiourea, N,N'-dicyclohexylthiourea, trimethylthiourea, triethylthiourea, tri-n-propylthiourea, tricyclohexylthiourea, tetramethylthiourea, tetraethylthiourea, tetra-n-propylthiourea, and tetracyclohexylthiourea.
[0115] When the dental curable composition of the present invention contains a polymerization accelerator (E), its content is not particularly limited, but from the viewpoint of the curability of the obtained dental curable composition, it is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, even more preferably 0.02 parts by mass or more, and may be 0.03 parts by mass or more, 0.05 parts by mass or more, or even 0.1 parts by mass or more, relative to 100 parts by mass of the total mass of the polymerizable monomer (A), since precipitation may occur in the dental curable composition if the content of the polymerization accelerator (E) is too high, the content of the polymerization accelerator (E) is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, particularly preferably 5 parts by mass or less, and may be 2 parts by mass or less, 1 part by mass or less, or even 0.5 parts by mass or less, relative to 100 parts by mass of the total mass of the polymerizable monomer (A).
[0116] [Additive (F)] The dental curable composition of the present invention may further contain, as necessary, additives (F) such as polymerization inhibitors, ultraviolet absorbers, antioxidants, antibacterial agents, dispersants, pH adjusters, pigments, dyes, etc., in addition to the above-mentioned polymerizable monomers (A), inorganic fillers (B), polymerization initiators (C), fluorescent agents (D), and polymerization accelerators (E). The additives (F) may be used alone or in combination of two or more.
[0117] Examples of the polymerization inhibitor include 3,5-di-t-butyl-4-hydroxytoluene, hydroquinone, dibutyl hydroquinone, dibutyl hydroquinone monomethyl ether, hydroquinone monomethyl ether, and 2,6-di-t-butylphenol, and these may be used alone or in combination of two or more. Examples of the ultraviolet absorber include benzotriazole compounds such as 2-(2-hydroxyphenyl)benzotriazole, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-ethylphenyl)benzotriazole, 2-(2-hydroxy-5-propylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, and 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chloro-2H-benzotriazole (Tinuvin 326), and benzimidazole compounds, and these may be used alone or in combination of two or more.
[0118] <<Method for producing dental hardenable composition>> The method for producing the dental hardenable composition of the present invention is not particularly limited, and the dental hardenable composition can be obtained by mixing each component in a predetermined amount. The order of mixing is not particularly limited, and each component may be mixed at once or may be mixed in two or more batches. In addition, the components may be mixed or kneaded as necessary, or may be subjected to a degassing treatment such as a vacuum degassing treatment. The obtained dental hardenable composition can be filled into a single container (such as a syringe) to form a one-material (one-paste) dental hardenable composition.
[0119] 《Application》 The dental hardenable composition of the present invention and its hardened product are not particularly limited in use and can be used as various dental materials, specifically, it can be preferably used as dental composite resins (e.g., composite resins for filling dental cavities, composite resins for core construction, composite resins for crowns, etc.), denture base resins, denture base lining materials, impression materials, luting materials (e.g., resin cements, resin-added glass ionomer cements, etc.), dental adhesives (e.g., orthodontic adhesives, cavity coating adhesives, etc.), fissure sealants, CAD / CAM resin blocks, temporary crowns, artificial tooth materials, etc. Among these, the dental hardenable composition of the present invention is particularly preferably used as dental composite resins and CAD / CAM resin blocks because of its high aesthetics and excellent mechanical strength.
[0120] The present invention includes embodiments in which the above configurations are combined in various ways within the scope of the technical concept of the present invention, as long as the effects of the present invention are achieved. EXAMPLES
[0121] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. Test methods, materials, etc. used in the examples are summarized below.
[0122] Test Method [Average particle size of filler] For the fillers listed below, the average particle size was measured on a volume basis using a laser diffraction particle size analyzer (Shimadzu Corporation, "SALD-2300") with ethanol as the dispersion medium, or using a scanning electron microscope (Hitachi High-Technologies Corporation, SU3500) (N=1).
[0123] [Specific surface area of inorganic filler] The inorganic fillers obtained in each of the following manufacturing examples were treated in an electric furnace at 450°C for 4 hours to be incinerated, and then subjected to vacuum degassing at 100°C for 2 hours. The specific surface area of the inorganic fillers was then measured (N=1) using a specific surface area measuring device (Microtrack-Bell Corporation's "BELSORP-mini II") under the conditions of adsorption gas: nitrogen, measurement temperature: 77K. Note that in this measurement, analysis was performed by the BET multipoint method using five points on the adsorption side isotherm where the ratio (P / P0) of the adsorption equilibrium pressure P (kPa) to the saturated vapor pressure P0 (kPa) was in the range of 0.05 to 0.3.
[0124] [Mechanical strength (flexural strength): dental composite resin] The dental curable compositions of each of the examples and comparative examples were vacuum degassed, filled into a stainless steel mold (dimensions: 2 mm x 2 mm x 25 mm), pressed against each other with slide glass, and cured by irradiating light to both sides, 5 points on each side, for 10 seconds at each point, with a dental visible light irradiator (Pencure 2000, manufactured by Morita Corporation). Five test pieces of the cured product were prepared for each of the examples and comparative examples. The test pieces of the cured product were removed from the mold and stored in distilled water at 37 ° C. for 24 hours. For each test piece, the three-point bending strength of the test piece of the cured product was measured using a universal testing machine (manufactured by Shimadzu Corporation, product name "AG-I 100kN") according to JIS T 6514:2015 and ISO4049:2019 under conditions of a support distance of 20 mm and a crosshead speed of 1 mm / min, and the average value of the measured values of each test piece was calculated to be the bending strength. The bending strength is preferably 100 MPa or more, more preferably 110 MPa or more, and even more preferably 120 MPa or more.
[0125] [Mechanical strength (flexural strength): dental mill blanks] Ten test pieces (1.2 mm x 4 mm x 14 mm) were prepared from the hardened products of the dental hardenable compositions of each Example and Comparative Example using a diamond cutter, and immersed in distilled water at 37 ° C. for 24 hours. For each test piece, the three-point bending strength of the test piece of the hardened product was measured under the conditions of a support distance of 12 mm and a crosshead speed of 1 mm / min using a universal testing machine (manufactured by Shimadzu Corporation, product name "AG-I 100kN") according to JDMAS 245: 2017 (resin material for dental cutting processing for CAD / CAM crowns), and the average value of the measured values of each test piece was calculated and used as the bending strength (N = 10). The bending strength is preferably 150 MPa or more, more preferably 165 MPa or more, and even more preferably 180 MPa or more.
[0126] [Color of hardened product: Dental composite resin] A cover glass was placed on the slide glass, and a stainless steel mold with a diameter of 10 mm and a thickness of 1 mm was placed on top of the cover glass. The dental composite material obtained in each Example and Comparative Example was filled into the mold until it overflowed a little. A cover glass was placed on top of the cover glass, and then a slide glass was placed on top of the cover glass, and a force was applied from above to push out the excess dental composite material from the mold. The material was irradiated with a dental visible light irradiator (Pencure 2000, manufactured by Morita Co., Ltd.) for 10 seconds to harden it, and the cover glass, slide glass, and mold were removed to obtain a test piece of the hardened material.
[0127] The color tone of the cured product was evaluated using a spectrophotometer (SE6000, manufactured by Nippon Denshoku Industries Co., Ltd.). Specifically, the L of JIS Z 8781-4:2013 was used when measuring the chromaticity with a standard white board placed behind the test piece. * a * b * Lightness index L in color system * Represents the lightness (L * / w), chromaticity a * and b * Chromaticity (a * / w and b * / w), and L when the chromaticity is measured with a standard blackboard placed behind the same test piece. * a * b * Lightness index L in color system* Represents the lightness (L * / b) was measured. * / w and L * Difference in / b: ΔL * was calculated and used as an index of transparency (N=1).
[0128] [Color of hardened material: dental mill blank] From the hardened product of the dental hardenable composition of each Example and Comparative Example, a plate-shaped test piece (10 mm x 10 mm x 1.2 mm) was cut out using a diamond cutter, and the smooth surface was polished under dry conditions with #1500 abrasive paper, #2000 abrasive paper, and #3000 abrasive paper in that order, and the final thickness was adjusted to 1.0 mm. The color tone of this test piece was measured using a spectrophotometer (SE6000, manufactured by Nippon Denshoku Industries Co., Ltd.) in the same manner as in the case of the dental composite resin (N=1).
[0129] In both dental composite resin and dental mill blanks, L * From the viewpoint of aesthetics, / w is preferably 80 or more, more preferably 82 or more, even more preferably 85 or more, and particularly preferably 87 or more, and the upper limit may be 98 or less. * / w represents redness, and the lower the value, the stronger the greenness, and the higher the value, the stronger the redness. From the viewpoint of aesthetics, a value of more than -10 is preferable, a value of -9 or more is more preferable, and a value of -8 or more is even more preferable. * / w is preferably 8 or less, more preferably 7 or less, and even more preferably 5 or less. * / w represents a yellowness index, the lower the value, the stronger the blueness, and the higher the value, the stronger the yellowness. From the viewpoint of aesthetics, it is preferably 0 or more, more preferably 2 or more, and even more preferably 5 or more. * / w is preferably 30 or less, more preferably 25 or less, and even more preferably 20 or less. * A higher value means higher transparency. From the viewpoint of aesthetics, a value of 15 or more is preferable, a value of 20 or more is more preferable, and a value of 25 or more is even more preferable. The upper limit may be 50 or less.
[0130] [Discoloration resistance of the cured product] For both dental composite resin and dental mill blank, three test pieces were prepared in the same manner as for the evaluation of the color tone of the cured product, and the L was measured in the same manner. * / w,a * / w and b * The value of / w was measured and used as the initial lightness and chromaticity. One of the test pieces was stored in water at 37°C, and the other in dry conditions at 60°C for 30 days. The remaining test piece was exposed to a xenon lamp with an illuminance of 150,000lx in water for 24 hours using an accelerated weathering tester (SOLARBOX 1500e, manufactured by CO.FO.ME.GRA) for a durability test. The L of each test piece after these durability tests was * / w,a * / w and b * / w, and the difference between the initial lightness and chromaticity ΔL * , Δa * and Δb * Furthermore, the color difference ΔE * = {(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2 The value was used as an index of discoloration resistance after each durability test. * The lower the value, the higher the color fastness, and it is preferably 7 or less, more preferably 6 or less, and even more preferably 5 or less. In Table 1, the measurement results of the test piece stored under 37°C underwater conditions for 30 days are represented as "cured product 37°C 30 days wet", the measurement results of the test piece stored under 60°C dry conditions for 30 days are represented as "cured product 60°C 30 days dry", and the measurement results of the test piece exposed to water and xenon lamp irradiation for 24 hours are represented as "after Suntest". The "initial" means the test piece before storage under water conditions for the test piece stored under 37°C underwater conditions for 30 days, the test piece before storage under dry conditions for the test piece stored under 60°C dry conditions for 30 days, and the test piece before irradiation with the xenon lamp for the test piece irradiated with the xenon lamp.
[0131] [Fluorescence of the cured product] In both cases of dental composite resin and dental mill blank, one test piece of the cured product was prepared in the same manner as in the evaluation of the color tone of the cured product. In addition, human extracted teeth were polished to prepare a human tooth test piece with a thickness of 1 mm. The test piece of the cured product and the human tooth test piece were observed under irradiation with a black light (FL20S BLB, manufactured by Toshiba Lighting & Technology Corporation), and the fluorescence intensity was visually compared and scored. That is, the score was "2" if the fluorescence intensity of the test piece of the cured product was equivalent to that of the human tooth test piece, "1" if the fluorescence intensity was inferior, and "0" if no fluorescence was observed. In addition, this test piece was exposed to xenon lamp irradiation for 24 hours in the same manner as in the evaluation of the discoloration resistance of the cured product, and the fluorescence score was evaluated in the same manner. It is preferable that the fluorescence score is 2. In Table 1, the measurement results of the test piece before 24 hours of exposure to xenon lamp irradiation are represented as "initial", and the measurement results after 24 hours of exposure to xenon lamp irradiation are represented as "after Suntest".
[0132] [Abrasiveability of the cured product] For dental composite resin, a dental curable composition obtained in each Example and Comparative Example was filled into a tetrafluoroethylene mold (inner diameter 10 mm x thickness 2.0 mm), irradiated with light for 10 seconds using a dental visible light irradiator (Pencure 2000, manufactured by Morita Corporation), and the cured product was removed from the mold to prepare a test specimen. For dental mill blanks, a diamond cutter was used to cut the blanks into plates (10 mm x 10 mm x 2.0 mm) to prepare test specimens. The smooth surfaces of these test specimens were polished with #600 abrasive paper under dry conditions. Furthermore, using a "Volvere RX" (manufactured by NSK Corporation) as a laboratory engine, the specimens were polished under wet conditions using a brown silicone point ("M2 HP" manufactured by Matsukaze Corporation) at a rotation speed of about 5,000 rpm for 10 seconds, and then polished with a blue silicone point ("M3 HP" manufactured by Matsukaze Corporation) at a rotation speed of about 5,000 rpm for 10 seconds. The gloss of the polished surface was then measured using a gloss meter ("VG-2000" manufactured by Nippon Denshoku Industries Co., Ltd., measuring angle 60 degrees) to determine the ratio (glossiness) to the mirror being taken as 100%, which was used as an index of the polishability of the cured product (N=3). The glossiness is preferably 30% or more, more preferably 35% or more, even more preferably 40% or more, and particularly preferably 50% or more.
[0133] [Method for measuring X-ray contrast property of cured product] For the dental composite resin, the dental curable composition was cured using a dental visible light irradiator (Pencure 2000, manufactured by Morita Corporation) to prepare a test piece (φ1.5 mm×1.0 mm) of the cured product. For the dental mill blank, a diamond cutter was used to cut out a plate (10 mm×10 mm×1.0 mm) to prepare a test piece. The test piece was placed next to an aluminum step wedge in the center of an X-ray film (Carestream Health Corporation, occlusal type "Ultraspeed DF-50"), and X-ray irradiation was performed using a digital X-ray device (Morita Manufacturing Co., Ltd., "Max DC70") under the conditions of a target-film distance of 400 mm and a tube voltage of 70 kV. After the film after irradiation was developed, fixed and dried, the image density of the test piece was measured at 20 points using an optical densitometer (Kodak's DENSITOMETER, "PDA-85", measurement area (3 mmφ)), and the image density of the test piece was compared with the image density of the aluminum step wedge at each thickness to obtain the X-ray contrast corresponding to the thickness of the aluminum plate (N=1). The X-ray contrast is preferably 1.0 mm or more, more preferably 1.3 mm or more, even more preferably 1.5 mm or more, and may be 2.0 mm or more, or may be 3.0 mm or more.
[0134] "material" (Polymerizable monomer (A)) D2.6E: 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (average number of moles of ethyleneoxy groups added: 2.6) Bis-GMA: 2,2-bis[4-(3-methacryloyloxy-2-hydroxypropoxy)phenyl]propane UDMA: 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate 3G: Triethylene glycol dimethacrylate TCDDMA: Tricyclodecane dimethanol dimethacrylate
[0135] (Inorganic filler (B)) The fillers used were those obtained in the following Production Examples. Commercially available products were used as they were.
[0136] [Production Example 1] ·Manufacture of B-1 (silica-zirconia) 32.5 g of zirconium oxynitrate was dissolved in 325 g of distilled water. While stirring this solution, 425 g of commercially available silica sol (Nissan Chemical Industries, Ltd.'s "Snowtex OL") was gradually added to obtain a mixed solution. The mixed powder obtained by freeze-drying this mixed solution was placed in an alumina crucible, heated in an electric furnace at a heating rate of 2°C / min, and then fired at 600°C for 1 hour, and then ground for 240 minutes in a planetary ball mill (Fritsch, "Classic Line P-6", zirconia balls). The ground powder was hydrophobized by surface treatment with 10 parts by mass of 3-methacryloyloxypropyltrimethoxysilane (KBM-503, Shin-Etsu Chemical Co., Ltd.) per 100 parts by mass of the powder, to obtain an inorganic filler (B-1). The average particle size of the obtained inorganic filler (B-1) was 3.0 μm, and the specific surface area was 146 m 2 / g.
[0137] [Production Example 2] · Manufacture of B-2 (alumina) Alumina fine powder (AEROXIDE Alu C, manufactured by Nippon Aerosil Co., Ltd.) was surface-treated with 20 parts by mass of γ-methacryloxypropyltrimethoxysilane (KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts by mass to obtain an inorganic filler (B-2). The average particle diameter of the obtained inorganic filler (B-2) was 0.02 μm. 2 / g.
[0138] [Production Example 3] ·Manufacture of B-3 (barium glass) 100 parts by mass of commercially available barium glass (GM27884 NanoFine180, manufactured by Schott), 7 parts by mass of 3-methacryloyloxypropyltrimethoxysilane (KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.), and 173 parts by mass of toluene were placed in a three-neck flask and stirred at room temperature for 2 hours. After the toluene was distilled off under reduced pressure, the mixture was vacuum dried at 40°C for 16 hours and further heated at 90°C for 3 hours to obtain an inorganic filler (B-3) provided with a surface treatment layer. The average particle diameter of the obtained inorganic filler (B-3) was 0.2 μm and the specific surface area was 35 m 2 / g.
[0139] [Production Example 4] ·Manufacture of B-4 (organic-inorganic composite filler) 100 parts by mass of the inorganic filler (B-3) produced above was added as an inorganic filler to 100 parts by mass of a polymerizable monomer mixture (mass ratio 1:1) of Bis-GMA and 3G in which 1% by mass of azobisisobutyronitrile (AIBN) was dissolved as a polymerization initiator in advance, and the mixture was mixed to form a paste. This was heated and polymerized at 100°C under a reduced pressure atmosphere for 5 hours. The obtained polymerized and cured product was pulverized using a vibration ball mill until the average particle size was about 5 μm. 100 parts by mass of the obtained powder was subjected to surface treatment by refluxing at 90°C for 5 hours in an ethanol solution containing 2% by mass of γ-methacryloyloxypropyltrimethoxysilane (KBM-503, Shin-Etsu Chemical Co., Ltd.), to obtain an inorganic filler (B-4) which is an organic-inorganic composite filler. The average particle size of the obtained inorganic filler (B-4) was 5.2 μm and the specific surface area was 35 m 2 / g.
[0140] [Production Example 5] ·Manufacture of B-5 (Silica-Ytterbia) The water in a commercially available silica-ytterbium oxide aqueous dispersion (SG-YBSO30SW, manufactured by Sukgyung AT) was distilled off using an evaporator, and the obtained solid component was ground for 180 minutes using a planetary ball mill (manufactured by Fritsch, "Classic Line P-6", zirconia balls). The obtained powder was fired for 1 hour in an electric furnace set at 800°C, and then ground for 180 minutes using the planetary ball mill. The obtained powder was surface-treated with 10 parts by mass of 3-methacryloyloxypropyltrimethoxysilane (KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts by mass to be hydrophobic, thereby obtaining an inorganic filler (B-5). The obtained inorganic filler (B-5) had an average particle size of 5.7 μm and a specific surface area of 95.8 m 2 / g.
[0141] B-6 (Ytterbium Fluoride) Silica-coated ytterbium fluoride (SG-YBF100WSCMP10, manufactured by Sukgyung AT) was used as is. The average particle size was 100 nm and the specific surface area was 14.2 m 2 / g.
[0142] (Polymerization initiator (C)) CQ: Camphorquinone TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide THP: 1,1,3,3-tetramethylbutyl hydroperoxide
[0143] (Fluorescent agent (D-1)) D-1-1: 2-(2-hydroxyphenyl)-4(1H)-quinazolinone (formula (9)) [ka] D-1-2: N-[2-(4-oxo-1,3-benzoxazin-2-yl)phenyl]benzenesulfonamide (formula (10)) [ka] D-1-3: 7-Dimethylamino-3-[2-[4-(trifluoromethyl)phenyl]ethenyl]-2H-1,4-benzoxazin-2-one (formula (11)) [ka]
[0144] (Fluorescent agent (D-2)) D-2-1: 1,4-bis(2-benzoxazolyl)naphthalene (formula (12)) [ka]
[0145] (Fluorescent agent (D-3)) D-3-1: Diethyl 2,5-dihydroxyterephthalate
[0146] (Polymerization accelerator (E)) PDE: Ethyl 4-(N,N-dimethylamino)benzoate
[0147] (Additive (F)) BHT: 3,5-di-t-butyl-4-hydroxytoluene (polymerization inhibitor) TIN: "Tinuvin 326" (manufactured by BASF Japan Ltd.) (ultraviolet absorber)
[0148] [Examples 1 to 6 and Comparative Examples 1 to 6] (Dental composite resin) The materials and ratios shown in Table 1 were mixed and kneaded at room temperature (23°C) in a dark place, and the homogenized material was vacuum degassed to prepare dental hardenable compositions. Each test was carried out on these dental hardenable compositions by the above-mentioned methods. The results are shown in Table 1.
[0149] [Example 7 and Comparative Examples 7 and 8] (Dental Mill Blanks) The materials and ratios shown in Table 1 were mixed and kneaded at room temperature (23°C) in a dark place, and the homogenized material was vacuum degassed to prepare dental hardenable compositions. The dental hardenable compositions were then poured into a rectangular mold measuring 20mm x 30mm x 60mm and heated at 50°C for 1 hour. After that, the mixture was pressurized at 5MPa and heated at 150°C for 1 hour to obtain hardened products as dental mill blanks. The hardened products of these dental hardenable compositions were subjected to the tests described above. The results are shown in Table 1.
[0150] [Table 1]
[0151] As shown in Table 1, the dental curable composition of the present invention has a good color tone after curing, is excellent in discoloration resistance, and does not lose its fluorescence even after a light resistance test. In particular, in Example 5, it was confirmed that discoloration (yellowing) of the cured product was suppressed despite the inclusion of alumina as an inorganic filler. In addition, it is found that the dental curable composition of the present invention has a high bending strength after curing, and sufficient gloss is generated by simple polishing, and has good polishability. [Industrial Applicability]
[0152] The dental curable composition of the present invention is suitable for use as a dental composite resin or a dental mill blank, since the cured product has sufficient fluorescence, excellent aesthetics and durability, sufficient mechanical strength, and does not impair ease of polishing.
Claims
1. The composition comprises a polymerizable monomer (A), an inorganic filler (B), a polymerization initiator (C), and a fluorescent agent (D), the fluorescent agent (D) comprising a 9- to 11-membered benzo-fused heterocycle-containing compound (excluding benzimidazole compounds) containing two or more heteroatoms; The 9- to 11-membered benzo-fused heterocyclic ring-containing compound containing two or more heteroatoms includes a fluorescent agent (D-1) which is a 6-membered benzo-fused heterocyclic ring-containing compound containing two heteroatoms; The dental curable composition, wherein the fluorescent agent (D-1) is a compound having a moiety represented by the following general formula (1) or (2): 【Chemistry 1】 【Chemistry 2】 (In general formulas (1) and (2), R 1 represents an oxygen atom or —NH—, and R 2 represents an aromatic group which may have a substituent.)
2. The fluorescent agent (D-1) is 2-(2-hydroxyphenyl)-4(1H)-quinazolinone, 2-(2-hydroxyphenyl)-4H-3,1-benzoxazin-4-one, N-[2-(4(1H)-quinazolinon-2-yl)phenyl]benzenesulfonamide, N-[2-(4-oxo-1,3-benzoxazin-2-yl)phenyl]benzenesulfonamide, 7-dimethylamino-3-[2-[4-(trifluoromethyl)phenyl]ethane 2. The dental hardenable composition according to claim 1, comprising at least one compound selected from the group consisting of 7-dimethylamino-3-[2-[2,3,4,5,6-pentafluorophenyl]ethenyl]-2H-1,4-benzoxazin-2-one, 7-dimethylamino-3-[2-[2,4-bis(trifluoromethyl)phenyl]ethenyl]-2H-1,4-benzoxazin-2-one, and 7-dimethylamino-3-[2-[2,4-bis(trifluoromethyl)phenyl]ethenyl]-2H-1,4-benzoxazin-2-one.
3. 3. The dental hardenable composition according to claim 1, wherein the fluorescent agent (D) further comprises a fluorescent agent (D-2) which is a benzo-fused heterocyclic 5-membered ring-containing compound containing one nitrogen atom and one oxygen atom.
4. The dental hardenable composition according to claim 3, wherein the fluorescent agent (D-2) is a fluorescent agent (D-2a) that is a compound containing a benzoxazole skeleton.
5. The dental curable composition according to claim 4, wherein the fluorescent agent (D-2a) is a compound having a moiety represented by the following general formula (3): 【Chemistry 5】 (In general formula (3), R 3 represents an aromatic group which may have a substituent, or a vinylene group which may have a substituent.
6. The dental curable composition according to claim 4 or 5, wherein the fluorescent agent (D-2a) is a compound represented by the following formula (12): 【Chemistry 6】
7. The dental hardenable composition according to any one of claims 1 to 6, wherein the inorganic filler (B) is an inorganic filler containing at least one metal compound selected from the group consisting of zirconium oxide, aluminum oxide, ytterbium oxide, and ytterbium fluoride.
8. The specific surface area of the inorganic filler (B) is 10 to 300 m 2 The dental hardenable composition according to any one of claims 1 to 7, wherein the composition is a hardener having a viscosity of 1000:1 or more.
9. A dental composite resin, comprising the dental hardenable composition according to any one of claims 1 to 8.
10. A dental mill blank comprising a cured product of the dental hardenable composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Non-radiation impermeable,slouride releasing and visible ray hardening dental composite and use of specified filler in the composite
JP1990233605A
Curable composition for dental use
JP2002255722A
Benzoxazinone-based compound, pigment and organic electroluminescent element
JP2009215443A
Photopolymerizable composition
JP2009280673A
Fluorescent zirconia material
JP2010222466A